Carbon-coated timn-based hydrogen storage alloy particles with inter-particle thermal bridge network, preparation and application thereof

By constructing an internally bonded carbon layer and an external thermal bridge carbon layer on the surface of TiMn-based hydrogen storage alloy particles, a thermal bridge network between particles is formed, which solves the problems of low thermal conductivity and poor cycle stability of TiMn-based hydrogen storage alloy beds, and achieves more efficient thermal management and oxidation resistance.

CN123039338APending Publication Date: 2026-11-06DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611348402.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

TiMn-based hydrogen storage alloys face thermal management challenges in engineering applications, particularly due to low effective thermal conductivity of the bed caused by interparticle point contact and deterioration of particle contact during cycling, which affects hydrogen absorption/desorption rates and stability.

Method used

An inner bonding carbon layer and an outer thermal bridge carbon layer are constructed on the surface of TiMn-based hydrogen storage alloy particles to form a composite carbon coating structure. The inner bonding carbon layer is used to fix the outer thermal bridge carbon material, while the outer thermal bridge carbon layer is exposed on the particle surface to form an inter-particle thermal bridge network.

Benefits of technology

It improves the effective thermal conductivity of the hydrogen storage alloy particle bed, enhances the thermal management of the hydrogen absorption and desorption processes, strengthens the oxidation resistance and cycle stability, reduces particle pulverization, and maintains the gas permeability and hydrogen storage capacity of the bed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123039338A_ABST
    Figure CN123039338A_ABST
Patent Text Reader

Abstract

This application relates to the fields of solid-state hydrogen storage materials and thermal management technology of hydrogen storage beds, specifically to a carbon-coated TiMn-based hydrogen storage alloy particle, its preparation method and application. By constructing an internally bonded carbon layer and an external thermal bridge carbon layer on the surface of millimeter-sized TiMn-based hydrogen storage alloy particles, the effective thermal conductivity, hydrogen absorption and desorption thermal management capability and cycle stability of the TiMn-based hydrogen storage alloy particle bed are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the fields of solid-state hydrogen storage materials and thermal management technology for hydrogen storage beds, specifically to a carbon-coated TiMn-based hydrogen storage alloy particle, its preparation method, and its application. In particular, it relates to a hydrogen storage material that improves the effective thermal conductivity, hydrogen absorption and desorption thermal management capability, and cycle stability of the TiMn-based hydrogen storage alloy particle bed by constructing an internally bonded carbon layer and an external thermal bridge carbon layer on the surface of millimeter-scale TiMn-based hydrogen storage alloy particles. Background Technology

[0002] TiMn-based hydrogen storage alloys are a class of reversible metal hydride hydrogen storage materials with practical application potential. They feature adjustable hydrogen absorption / desorption plateau pressures, relatively low cost, good cycle performance, and suitability for engineered hydrogen storage devices. By adjusting the Ti / Mn ratio and introducing elements such as Cr, V, Fe, Zr, Ni, and Co, their plateau pressure, capacity, and cycle stability can be further controlled. Therefore, TiMn-based hydrogen storage alloys can be used in stationary hydrogen storage devices, hydrogen compression devices, fuel cell hydrogen supply systems, and mobile hydrogen source systems.

[0003] However, TiMn-based hydrogen storage alloys present significant thermal management challenges in engineering applications. The hydrogen absorption process of metal hydrides is typically exothermic, while the hydrogen release process is typically endothermic. During hydrogen absorption, if the heat of reaction cannot be dissipated from the material bed in a timely manner, the localized temperature rise will reduce the driving force for hydrogen absorption, thus decreasing the absorption rate. Conversely, during hydrogen release, if external heat cannot be transferred to the material particles and the bed interior in a timely manner, it will lead to a localized temperature drop, further reducing the hydrogen release rate.

[0004] For practical TiMn-based hydrogen storage alloy particle beds, the main factor limiting heat transfer is often not the individual alloy particles themselves, but the contact interfaces formed after particle stacking. Heat transfer between millimeter-sized TiMn-based hydrogen storage alloy particles mainly occurs through point contact. The presence of numerous pores and gas phase spaces between particles results in an effective thermal conductivity significantly lower than that of dense metal materials.

[0005] Furthermore, TiMn-based hydrogen storage alloys undergo volume expansion and contraction during hydrogen absorption and desorption cycles, making the particles prone to cracking and pulverization. The pulverized fine powder alters the bed pore structure and interparticle contact state, increasing interparticle contact thermal resistance, which further leads to a decrease in bed thermal conductivity, an increase in pressure drop, and a decrease in hydrogen charge / decharge rates.

[0006] Existing technologies typically improve bed heat transfer by incorporating reactor-level components such as heat exchange tubes, heat-conducting fins, honeycomb structures, metal foams, or metal meshes into hydrogen storage containers. While these methods can enhance localized heat transfer capacity, they increase the structural complexity and ineffective mass of the device and may reduce the amount of hydrogen storage material packed per unit volume.

[0007] Another approach involves mixing metal hydride powder with expanded graphite, graphite, carbon materials, or metal powder and then compacting the mixture to improve the thermal conductivity of the compacted material. However, this method is primarily suitable for powder or compacted systems and is not ideal for maintaining the independent particle morphology of TiMn-based hydrogen storage alloy engineering particles with a particle size of 0.6–0.85 mm. Compaction can also alter the gas channels in the bed, affecting hydrogen transport and the flexibility of filling and maintenance.

[0008] Other surface coating methods are primarily used to improve the oxidation resistance of hydrogen storage alloys, such as polymer coatings or ordinary carbon film coatings. These coatings can reduce the effects of air and moisture on the alloy surface to some extent, but their core function is usually not to establish an interparticle thermal conductivity network. If the coating itself has low thermal conductivity or is too dense, it may also increase interparticle thermal resistance or hinder hydrogen transport.

[0009] Therefore, there is an urgent need to develop a surface modification method suitable for millimeter-scale TiMn-based hydrogen storage alloy engineering particles, which can establish a stable thermal conduction path from the particle contact interface without compacting the particles, significantly sacrificing the gas permeability and reversible hydrogen storage capacity of the bed, thereby improving the effective thermal conductivity of the hydrogen storage bed, while taking into account air stability and cycle anti-pulverization ability. Summary of the Invention

[0010] The purpose of this application is to provide a carbon-coated TiMn-based hydrogen storage alloy particle with an interparticle thermal bridge network, its preparation method and application, in order to solve the problem of insufficient effective thermal conductivity of TiMn-based hydrogen storage alloy engineering particles in solid hydrogen storage beds due to point contact between particles, limited contribution of gas phase thermal conductivity in bed pores and deterioration of particle contact state caused by cyclic hydrogen absorption and desorption.

[0011] The following technical solution is adopted in this application.

[0012] According to one aspect of this application, carbon-coated TiMn-based hydrogen storage alloy particles are provided. The carbon-coated TiMn-based hydrogen storage alloy particles include a TiMn-based hydrogen storage alloy core, an inner bonding carbon layer disposed on the surface of the TiMn-based hydrogen storage alloy core, and an outer thermal bridge carbon layer disposed outside the inner bonding carbon layer.

[0013] A carbon-coated TiMn-based hydrogen storage alloy particle, comprising a TiMn-based hydrogen storage alloy core, an inner bonding carbon layer disposed on the surface of the TiMn-based hydrogen storage alloy core, and an outer thermal bridge carbon layer disposed on the outer surface of the inner bonding carbon layer away from the core.

[0014] Furthermore, the TiMn-based hydrogen storage alloy is TiMn, TiMn2, or TiMn. 1.5TiMn-based alloys containing one or more active phases selected from TiMnCr, TiMnV, and TiMnCrV, or the aforementioned active phases further containing one or more elements selected from Cr, V, Fe, Zr, Ni, Co, Mo, Al, La, and Ce. The TiMn-based hydrogen storage alloy particles have a particle size of 10–300 μm, preferably 20–100 μm, and more preferably 30–80 μm; preferably, the median particle size D of the TiMn-based hydrogen storage alloy particles is... 50 It is 40–65 μm.

[0015] Furthermore, the inner bonding carbon layer is formed by pyrolysis of one or more of phenolic resin (preferably methyl phenolic resin) or polydopamine. Different precursors are coated using separate, defined processes: phenolic resin is coated in the form of a solution or dispersion of an organic solvent; polydopamine is formed by in-situ oxidative polymerization of dopamine on the surface of TiMn particles in a weakly alkaline aqueous solution with a pH of 8.0–9.0 (preferably 8.5 ± 0.1); the inner bonding carbon layer is used to fix the external thermal bridge carbon material and buffer the interfacial stress of the TiMn-based hydrogen storage alloy during hydrogen absorption and desorption cycles. The thickness of the inner bonding carbon layer is 5–1000 nm, preferably 50–500 nm, and more preferably 100–300 nm; the inner bonding carbon layer may be a non-graphitized carbon layer derived from phenolic resin, or one or more of a nitrogen-containing carbon layer derived from polydopamine.

[0016] Furthermore, the external thermal bridge carbon layer comprises one or both of expanded graphite and graphene; the lateral dimension of the expanded graphite in the unloaded state is 5–30 μm, preferably 10–20 μm; its apparent sheet thickness is 0.2–3 μm, preferably 0.5–1.5 μm; the lateral dimension of the graphene in the unloaded state is 0.5–15 μm, preferably 2–8 μm, the sheet thickness is 1–30 nm, preferably 2–15 nm, and the number of layers is preferably 2–50, preferably 3–20. The median lateral dimension of the expanded graphite sheet is 5–30 μm, preferably 10–20 μm.

[0017] Furthermore, the external thermal bridge carbon layer is at least partially exposed on the outer surface of the particles, so that when multiple carbon-coated TiMn-based hydrogen storage alloy particles are stacked to form a hydrogen storage bed, the external thermal bridge carbon layers on the surfaces of adjacent particles can contact each other, overlap, entangle, or form surface contact, thereby forming a continuous or semi-continuous inter-particle thermal bridge network. Preferably, the ratio of the median lateral dimension of the expanded graphite sheet to the median particle size of the TiMn-based hydrogen storage alloy particle is 0.10 to 0.60, more preferably 0.20 to 0.40, so that the expanded graphite can adhere to the surface of a single TiMn particle and continuously overlap between adjacent particles through multiple sheets, rather than occupying the bed pores with excessively large independent agglomerates.

[0018] Furthermore, the total carbon content of the carbon-coated TiMn-based hydrogen storage alloy particles is 0.2–10 wt%, preferably 0.5–5 wt%, more preferably 0.8–3 wt%; the mass of expanded graphite and / or graphene in the external thermal bridge carbon layer is 0.1–5 wt% of the mass of the TiMn-based hydrogen storage alloy particles, preferably 0.3–3 wt%, more preferably 0.5–2 wt%.

[0019] Furthermore, the inner bonding carbon layer is not the main thermally conductive phase, but a non-graphitized carbon layer and / or nitrogen-doped carbon layer formed by the pyrolysis of phenolic resin and / or polydopamine, which is used to fix the external thermal bridge carbon material and provide a certain anti-oxidation and anti-pulverization buffer effect; the external thermal bridge carbon layer is the main thermally conductive phase, which forms a thermally conductive network between particles through lamellar overlap, tubular entanglement or surface contact.

[0020] Secondly, a method for preparing carbon-coated TiMn-based hydrogen storage alloy particles includes the following steps: (1) The TiMn-based hydrogen storage alloy is crushed and the particle size is controlled by standard sieving or air classification to obtain TiMn-based hydrogen storage alloy particles. The obtained TiMn-based hydrogen storage alloy particles were dried; after processing, they were cooled to room temperature under an inert atmosphere and stored in a sealed container. (2) An adhesive inner bonding layer is formed on the surface of TiMn-based hydrogen storage alloy particles: the precursor carbon source of the inner bonding layer is dopamine or phenolic resin. When the carbon source is phenolic resin, the phenolic resin is in the form of a solution, dispersion or flowable slurry of phenolic resin and is brought into contact with TiMn-based hydrogen storage alloy particles in a rolling state by spraying, dripping, impregnation or atomizing spraying, and then rolled coating is performed. 60% to 95% of the solvent is removed so that there is no free-flowing liquid on the particle surface and the particles remain dispersed and the inner bonding layer precursor layer has adhesiveness. When the carbon source is dopamine, TiMn-based hydrogen storage alloy particles are placed in an alkaline dopamine solution for in-situ oxidative polymerization. After filtration and rinsing, free polydopamine particles are removed and surface moisture is replaced, so that the particles are in a semi-wet state with a wet surface but no obvious free liquid. (3) Add the external thermal bridge carbon material to the particles obtained in step (2) while they are rolling, so that the external thermal bridge carbon material is attached to the outside of the inner adhesive layer. (4) After drying and pre-curing, carbonization is carried out to transform the inner bonding layer into a carbon-based inner bonding layer. At the same time, the external thermal bridge carbon material is fixed on the outer surface of the particles to obtain carbon-coated TiMn-based hydrogen storage alloy particles with the ability to construct inter-particle thermal bridge networks.

[0021] Furthermore, in step (1): TiMn-based hydrogen storage alloy particles with a particle size of 10–300 μm, preferably 20–100 μm, and more preferably 30–80 μm, are obtained by standard sieving or air classification. Preferably, the median particle size D of the particles is... 50 The thickness is 40–65 μm. The drying conditions are: vacuum drying at 80–120 °C and absolute pressure not higher than (less than or equal to) 100 Pa for 4–8 h, or treatment in an inert atmosphere at 80–200 °C for 1–4 h, or treatment in an H2 / Ar mixed atmosphere containing 1–10 vol.% H2 at 100–250 °C for 0.5–2 h, to remove adsorbed water, weakly adsorbed gases and loose surface impurities; The inert atmosphere is one or more of nitrogen and argon. In step (2): The phenolic resin solution is a phenolic resin solution with a solid mass fraction of 5-20 wt% obtained by mixing solid phenolic resin with anhydrous ethanol; if it is a commercial phenolic resin solution, the amount added is calculated according to its actual solid content, so that the amount of solid phenolic resin added is 0.2% to 8% of the mass of TiMn-based hydrogen storage alloy particles, preferably 0.5% to 5%, more preferably 1% to 3%; The alkaline dopamine solution is prepared by adding dopamine hydrochloride to a buffer solution to achieve a dopamine concentration of 1.0-3.0 mg / mL. The buffer solution is Tris buffer, and the pH is adjusted to 8.0-9.0, preferably 8.5±0.1. When the carbon source is phenolic resin, the rolling state is as follows: the TiMn-based hydrogen storage alloy particles are placed in the mixing device at a rotation speed of 10-80 rpm, preferably 20-50 rpm; the temperature of the TiMn-based hydrogen storage alloy particles is 15-60 ℃; and the rolling coating time is 10-120 min, preferably 30-60 min. When the carbon source is dopamine, the conditions for in-situ oxidative polymerization are 20-25 °C, low-speed rolling or slow mechanical stirring at 50-80 r / min for 30-120 min. In step (3): The rolling process is carried out in a mixing device at 15–60 °C and 10–80 rpm; the external heat bridge carbon material is added in stages, with rolling continuing for 3–10 minutes after each addition, and rolling continuing for 5–60 minutes after all the external heat bridge carbon material has been added; the amount of external heat bridge carbon material added is 0.1%–5% of the mass of the TiMn-based hydrogen storage alloy particles; Step (4) specifically includes: A. Drying and pre-curing: Vacuum drying at 60-90 ℃ for 2-12 h; followed by heat treatment from room temperature to the heat treatment temperature; The heat treatment atmosphere is preferably one or more of Ar, He, H2 volume concentration of 1-10% H2 / Ar or H2 volume concentration of 1-10% H2 / He; The heat treatment temperature is 110–180 ℃, preferably 120–180 ℃; the heat treatment time is 0.5–5 h, preferably 1–3 h; the heating rate is preferably 1–3 ℃ / min. B. Carbonization treatment: The pre-cured particles are heated to 200-300℃ and held at that temperature for 0.5-2 h, and then heated to the carbonization temperature for carbonization. The carbonization atmosphere is preferably one or more of Ar and He. The carbonization temperature is 400-700℃, preferably 500-600℃. The carbonization time is 0.5-5 h, preferably 1-3 h.

[0022] The mixing equipment is a drum coating equipment, disc coating equipment, V-shaped mixing equipment, or fluidized bed coating equipment that does not contain grinding media.

[0023] This application specifically emphasizes that the external thermal bridge carbon material is not simply physically mixed with TiMn-based hydrogen storage alloy particles after the inner bonding carbon layer has been completely carbonized. Instead, it is introduced while the inner bonding layer precursor still possesses bonding ability or is in a pre-cured state, allowing expanded graphite, carbon nanotubes, or graphene to be fixed to the surface of the TiMn-based hydrogen storage alloy particles. Therefore, the external thermal bridge carbon material can preferentially be located at the particle contact interface and form an inter-particle thermal conductive network.

[0024] According to a third aspect of this application, the above-mentioned carbon-coated TiMn-based hydrogen storage alloy particles are provided for use in solid-state hydrogen storage devices, hydrogen compression devices, fuel cell hydrogen supply systems, mobile hydrogen source systems, stationary energy storage systems, or metal hydride hydrogen storage beds.

[0025] The core advantage of this application lies in the fact that it does not simply mix carbon materials with TiMn-based hydrogen storage alloy particles, nor does it merely form a common protective carbon film on the particle surface. Instead, it constructs a composite carbon coating structure on the surface of TiMn-based hydrogen storage alloy particles, consisting of an inner bonding carbon layer and an outer thermal bridge carbon layer. The inner bonding carbon layer is used to stably fix the outer thermal bridge carbon material to the particle surface, and the outer thermal bridge carbon layer is at least partially exposed on the outer surface of the particles. This allows multiple particles to be stacked together and form an inter-particle thermal bridge network through overlapping, entanglement, or surface contact between expanded graphite, carbon nanotubes, or graphene.

[0026] Compared to existing technologies, the beneficial effects of this application are as follows: First, this application can improve the effective thermal conductivity of TiMn-based hydrogen storage alloy particle beds. After multiple carbon-coated particles are stacked, overlapping, entanglement, or surface contact occur between the external thermal bridge carbon layers, transforming the traditional particle point contact heat transfer into carbon material thermal bridge network heat transfer, thereby reducing the contact thermal resistance between particles.

[0027] Second, this application can improve the thermal management of the hydrogen absorption process. During the hydrogen absorption process, the TiMn-based hydrogen storage alloy releases reaction heat, and the interparticle thermal bridge network can promote the conduction of reaction heat from the inside of the bed to the outside, reduce local temperature rise and temperature gradient, and improve the hydrogen absorption rate and capacity utilization.

[0028] Third, this application can improve the heating capacity of the hydrogen release process. During the hydrogen release process, TiMn-based hydrogen storage alloys need to continuously absorb heat. The interparticle thermal bridge network can promote the transfer of external heat to the bed and the interior of the alloy particles, reduce the local low temperature zone, and improve the hydrogen release rate and hydrogen release stability.

[0029] Fourth, this application exhibits a synergistic antioxidant effect. The inner bonding carbon layer and the outer thermal bridge carbon layer together form a composite carbon coating structure, which can reduce the direct contact between oxygen and water vapor and the surface of the TiMn-based hydrogen storage alloy, thus delaying the oxidation of TiO2. x MnO x The formation of surface oxides improves the air stability of materials during crushing, screening, storage, transportation and loading processes.

[0030] Fifth, this application has a synergistic anti-pulverization effect. The inner bonding carbon layer can buffer the volume expansion and contraction stress of TiMn-based hydrogen storage alloy during hydrogen absorption and desorption cycles, while the outer thermal bridge carbon layer can form a flexible overlapping network on the particle surface, thereby reducing crack propagation and fine powder shedding, and slowing down the decay of bed thermal conductivity caused by cyclic pulverization.

[0031] Sixth, this application can achieve enhanced thermal conductivity with a lower carbon content. Since the external thermal bridge carbon material is fixed on the surface of TiMn particles and preferentially located at the particle contact interface, compared with simple physical mixing methods, this application can more easily form an effective thermal conductivity path with the same amount of carbon added, thereby reducing the dilution of hydrogen storage capacity caused by ineffective carbon addition. Attached Figure Description

[0032] Figure 1 The images shown are SEM and TEM images of the product obtained in Example 1.

[0033] SEM images of PF-C / EG composite-coated TiMn-based hydrogen storage alloy particles reveal distinct wrinkled and lamellar expanded graphite deposits on the TiMn alloy particle surface. Some of the expanded graphite extends along the particle surface, forming overlapping structures between adjacent particles. TEM images further show an amorphous internal bonding carbon layer approximately 10–20 nm thick outside the TiMn alloy core. The outer expanded graphite maintains a relatively clear lamellar graphite structure and is fixed to the alloy surface by the internal bonding carbon layer. These results indicate that the carbon layer formed after the pyrolysis of phenolic resin effectively fixes the expanded graphite, constructing a composite structure of "TiMn alloy core—phenolic resin-derived carbon bonding layer—expanded graphite external thermal bridge layer." The exposed expanded graphite lamellars facilitate the formation of thermally conductive overlaps between particles during particle stacking, thereby reducing particle contact thermal resistance and improving the effective thermal conductivity of the bed.

[0034] Figure 2 The images shown are SEM and TEM images of the product obtained in Example 2.

[0035] SEM images of PDA-C / EG composite-coated TiMn-based hydrogen storage alloy particles show a relatively uniform and continuous surface coating structure, with expanded graphite sheets dispersedly attached to the outer surface of the particles. Compared to the PF-C / EG sample, the PDA-derived carbon layer provides more uniform coverage of the particle surface, and the interfacial bonding between the expanded graphite and the alloy particles is tighter. TEM images reveal a continuous nitrogen-doped carbon layer with a thickness of approximately 5–15 nm formed on the outer side of the TiMn alloy core, with the expanded graphite sheets fixed to the outer side of this carbon layer and partially extending outward. These results indicate that polydopamine can form a uniform precursor coating on the TiMn particle surface, which transforms into a continuous nitrogen-doped carbon binder layer after carbonization, thereby improving the interfacial adhesion stability of the expanded graphite. This structure not only facilitates the construction of an interparticle thermal conductivity network but also reduces direct exposure of the alloy surface through the continuous carbon layer and buffers the interfacial stress generated by hydrogen absorption and desorption cycles, thus improving oxidation resistance and cyclic anti-pulverization performance. Detailed Implementation

[0036] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments. Unless otherwise specified, the raw materials used in the embodiments of the present application can all be purchased commercially.

[0037] The expanded graphite used was commercially available micro-flask expanded graphite with a lateral dimension of 15 μm and an apparent lateral thickness of 0.5–1.5 μm in its unloaded state. The median lateral dimension D50 of the expanded graphite microflakes used was 10–20 μm (again, 15 μm). The expanded graphite was vacuum dried at 80 °C for 4 h before use.

[0038] When preparing the above-mentioned micro flakes from worm-like expanded graphite, a wet intermittent shearing method can be used: expandable graphite is added to anhydrous ethanol at a ratio of 1 g: 100 mL, and a rotor-stator shearing disperser is used to shear at 3000 r / min for 2 min, stop for 1 min, and repeat 5 times, with a total effective shearing time of 10 min. The material temperature is controlled below 40 ℃. Subsequently, vacuum filtration is performed, and the material is vacuum dried at 80 ℃ for 4 h. Large agglomerates larger than 20-40 μm are removed by air classifying (or using a 20-40 μm sieve).

[0039] Example 1: Phenolic resin-derived carbon / expanded graphite composite coated TiMn-based hydrogen storage alloy particles (PF-C / EG) (1) In this embodiment, 100.0 g of commercial TiMn 1.5 The hydrogen storage alloy powder is used as a reference. The "TiMn" 1.5 "This indicates a nominal atomic ratio of Ti:Mn of 1:1.5; (If the actual commercial alloy contains Cr, V, Fe, or other adjusting elements, the composition should be replaced by the batch composition sheet or ICP-OES measured composition). The alloy was crushed and graded, and powder with a particle size of 30–80 μm was collected, with a median particle size of 50 μm. The powder was vacuum dried at 100 °C and an absolute pressure of less than 100 Pa for 6 h, and then cooled to room temperature under argon protection."

[0040] (2) The phenolic resin used is a thermosetting methyl phenolic resin. Preparation of the precursor of the inner adhesive layer: Weigh 2.00 g of methyl phenolic resin by solids, add it to 18.00 g of anhydrous ethanol, and mechanically stir for 30 min at room temperature to obtain a phenolic resin solution with a solid mass fraction of 10 wt%.

[0041] If a commercial phenolic resin solution is used, the amount added should be calculated based on its actual solid content to ensure that the solid mass of the phenolic resin is 2.0 wt% of the mass of the TiMn-based hydrogen storage alloy particles.

[0042] (3) Phenolic resin pre-coating: TiMn-based hydrogen storage alloy particles are placed in a SYH-1 type three-dimensional motion mixer (loading cylinder volume 1 L, or equipment with equivalent low-shear tumbling function) (roller coating device) and rolled at a speed of 40-60 r / min (50 r / min in this case). At room temperature, phenolic resin solution is uniformly sprayed onto the surface of the rolling particles using an atomizing nozzle within 10-15 min (14 min in this case). After spraying, rolling continues for 15 min to allow partial evaporation of ethanol and the formation of a uniform, viscous phenolic resin precursor layer on the particle surface. There should be no obvious free liquid or large-area adhesion of particles during the coating process.

[0043] (4) Fixation of external thermal bridge expanded graphite: Air was introduced to remove 75% of the solvent from the inner binder layer precursor on the surface of the TiMn-based hydrogen storage alloy particles (13.50 g of anhydrous ethanol was removed, leaving 4.50 g), so that there was no free-flowing liquid on the particle surface, the particles remained dispersed, and the inner binder layer precursor could still adhere to the powder. The resulting particles were then placed in a SYH-1 type three-dimensional motion mixer (1 L loading cylinder or a device with equivalent low-shear tumbling function). Weigh 1.00 g of the dried expanded graphite flakes (commercially micronized expanded graphite) and add them in four equal portions to the roller coating apparatus of step (3) at room temperature. After each addition, roll the apparatus at 40–60 r / min (50 r / min in this case) for 5 min. After all the flakes have been added, continue rolling at 40–60 r / min (50 r / min in this case) for 30 min. By adding the expanded graphite flakes in batches, the expanded graphite flakes adhere to the outer side of the still-adhesive phenolic resin precursor layer, while leaving some flakes exposed on the outer surface of the particles. The amount of expanded graphite added is 1.0 wt% of the mass of the TiMn-based hydrogen storage alloy particles.

[0044] (5) Drying and pre-curing: The coated particles are spread evenly in a quartz boat with a layer thickness not exceeding 10 mm (8 mm in this case), and dried in vacuum at 80 °C for 6 h. Then, under Ar atmosphere, the temperature is increased from room temperature to 120 °C at 1 °C / min and held for 1 h, and then increased to 160 °C at 1 °C / min and held for 2 h to allow the phenolic resin to fully cross-link and cure and to stably fix the expanded graphite on the particle surface.

[0045] Carbonization treatment: The pre-cured granules were placed in the constant temperature zone of a tube furnace. Ar with a volume purity of not less than 99.999% was introduced at a flow rate of 300 mL / min, and the temperature was raised after purging for 30 min. The temperature was increased to 200 °C at a rate of 2 °C / min and held for 1 h to facilitate the slow release of low molecular weight components; then the temperature was increased to 550 °C at a rate of 2 °C / min and held for 2 h to convert the phenolic resin into a non-graphitized internally bonded carbon layer with a thickness of 100–300 nm. After the holding period, the mixture was allowed to cool naturally to room temperature under Ar protection.

[0046] Performance Testing: The PF-C / EG composite-coated TiMn-based hydrogen storage alloy powder obtained in Example 1 was randomly and loosely packed into cylindrical sample cells of the same size (inner diameter 25 mm, effective height 35 mm, sample filling height 30±2 mm). The bed density deviation of each sample was controlled to be no more than ±2% using the same tapping procedure. The bed consisted of 30–80 μm composite particles and interparticle pores. The effective thermal conductivity of the bed was measured using the transient planar heat source method at 25±1 ℃ under a 0.10 MPa Ar atmosphere. Each sample was tested in triplicate, and the average value was taken. The effective thermal conductivity of the bed in Example 1 was 0.82 W / (m·K), which was approximately 49% higher than that of the uncoated TiMn sample (Comparative Example 1), and higher than the 0.68 W / (m·K) of the simple mixed expanded graphite sample (Comparative Example 2) and the 0.61 W / (m·K) of the sample coated only with phenolic resin-derived carbon (Comparative Example 3). In the sample obtained in this embodiment, the thickness of the inner bonding carbon layer is 100-300 nm, and the total carbon content is about 0.8-2.5 wt%.

[0047] Hydrogen absorption performance was tested using a QuantumCTek H-Sorb 2600PCT Pro device (inner diameter 25 mm, effective height 35 mm, sample loading height 30 ± 2 mm). After three activations, the sample was subjected to hydrogen absorption at 25.0 ± 0.5 °C and an initial hydrogen pressure of 3.0 MPa. The highest temperature rise in Example 1 decreased from 17.5 °C in the uncoated sample (Comparative Example 1) to 12.6 °C, and the time t required to reach 90% of the equilibrium hydrogen absorption capacity was [not specified]. 90 The reduction from 600 s to 410 s indicates that the interparticle thermal bridging network can promote the heat extraction of the hydrogen absorption reaction and improve the hydrogen absorption kinetics.

[0048] During the hydrogen absorption and desorption cycle, the sample absorbed hydrogen at 25 °C and 3.0 MPa for 30 min, and then desorbed hydrogen under vacuum conditions of 80 °C and 10 Pa for 60 min, repeating this cycle 100 times. After the cycle, the mass proportion of fine powder with a particle size less than 10 μm decreased from 16.0% in the uncoated sample (Comparative Example 1) to 8.0%, indicating that the phenolic resin-derived carbon layer can buffer the volume changes and interfacial stress caused by hydrogen absorption and desorption, and inhibit particle breakage and fine powder generation.

[0049] Air stability was evaluated using the reversible hydrogen absorption capacity retention rate. The reversible hydrogen absorption capacity measured before air exposure at 25 °C and 3.0 MPa hydrogen was taken as 100%. After exposing the sample to air at 25 ± 2 °C and 50 ± 10% relative humidity for 7 days, the hydrogen absorption capacity was remeasured under the same conditions. Example 1 showed a capacity retention rate of 90%, meaning that 90% of the reversible hydrogen absorption capacity before exposure was retained after exposure, indicating that the composite carbon coating structure can mitigate air oxidation and moisture passivation on the TiMn alloy surface.

[0050] The above results indicate that phenolic resin-derived carbon can stably fix expanded graphite onto the surface of TiMn particles and form an effective interparticle thermal bridge network after particle stacking, thereby synergistically improving the bed thermal conductivity, hydrogen absorption kinetics, cycle anti-pulverization ability and air stability.

[0051] Example 2: Polydopamine-derived nitrogen-doped carbon / expanded graphite composite coated TiMn-based hydrogen storage alloy particles (PDA-C / EG) This embodiment uses 100.0 g of commercial TiMn-based hydrogen storage alloy particles as a basis. The commercial TiMn-based hydrogen storage alloy was crushed and graded, collecting powder with a particle size of 30–80 μm. Before use, it was vacuum dried for 6 h at 100 °C and an absolute pressure not exceeding 100 Pa, and then cooled to room temperature in dry argon gas. A wet adhesive layer was first formed using the adhesion ability of polydopamine to metal and oxide surfaces, followed by fixation of expanded graphite and overall carbonization. The preparation was carried out according to the following steps: (1) Preparation of polydopamine deposition solution: Prepare 500 mL of Tris buffer with a concentration of 10 mmol / L, and adjust the pH to 8.5±0.1 with hydrochloric acid. Weigh 1.00 g of dopamine hydrochloride and add it to the buffer to make the dopamine concentration 2.0 mg / mL.

[0052] (2) Formation of the polydopamine wet binder layer: TiMn-based hydrogen storage alloy particles were added to a dopamine solution and rolled or mechanically stirred slowly at 50–80 r / min (60 r / min in this case) at 20–25 °C for 60 min to allow dopamine to undergo in-situ oxidative polymerization on the particle surface. After the reaction was completed, the mixture was immediately filtered, rinsed once with 100 mL of deionized water, and then rinsed twice with 100 mL of anhydrous ethanol to remove free polydopamine particles and replace surface moisture. After filtration, the particles were controlled to be in a semi-wet state with a moist surface but no obvious free liquid.

[0053] (3) Fixation of the expanded graphite external thermal bridge layer: The obtained semi-wet TiMn@PDA particles were transferred to a 500 mL roller coating container and rolled at 40–60 r / min (50 r / min in this case). 1.00 g of commercially available expanded graphite microsheets that had been vacuum dried at 80 ℃ for 4 h were weighed and added in 4 equal portions. After each addition, the mixture was rolled for 5 min. After all the microsheets were added, the mixture was rolled for another 30 min to fix the expanded graphite with the polydopamine wet layer and to expose some of the microsheets on the outer surface of the particles.

[0054] (4) Drying: The obtained particles were spread evenly in a quartz boat and dried under vacuum at 60 °C for 8 h; then vacuum dried at 90 °C for 2 h to remove residual water and ethanol as much as possible.

[0055] (5) Carbonization treatment: The dried particles were placed in the constant temperature zone of a tube furnace, and Ar with a purity of not less than 99.999% was introduced at a flow rate of 300 mL / min for 30 min. The temperature was increased to 300 °C at 2 °C / min and held for 1 h to slowly release the small molecules generated by the pyrolysis of polydopamine; then the temperature was increased to 550 °C at 2 °C / min and held for 2 h to convert polydopamine into a nitrogen-doped carbon inner binder layer. After carbonization, the particles were naturally cooled to room temperature under Ar protection.

[0056] Performance tests were conducted using the same method as in Example 1. Samples from Example 2 and all comparative examples were randomly packed using the same tapping procedure (process and conditions as in Example 1), controlling the bed volume density deviation to be no more than ±2%. The effective thermal conductivity of the bed was tested using the transient planar heat source method at 25±1 ℃ under a 0.10 MPa Ar atmosphere. The effective thermal conductivity of the bed in the Example 2 sample was 0.76 W / (m·K), approximately 38% higher than the 0.55 W / (m·K) of the uncoated TiMn sample. In the samples obtained in this example, the thickness of the inner bonding carbon layer was 100–300 nm, and the total carbon content was approximately 1.6–2.3 wt%.

[0057] After undergoing the same three hydrogen absorption and desorption activation processes, the samples were subjected to hydrogen absorption tests at 25.0 ± 0.5 °C and an initial hydrogen pressure of 3.0 MPa. In Example 2, the maximum temperature rise during hydrogen absorption decreased from 17.5 °C for the uncoated sample to 13.2 °C, and the time t90 required to reach 90% of the equilibrium hydrogen absorption capacity was shortened from 600 s to 440 s. This indicates that the PDA-C / EG structure can promote heat transfer during the hydrogen absorption reaction and improve hydrogen absorption kinetics.

[0058] In the cyclic test, the sample absorbed hydrogen at 25 °C and 3.0 MPa for 30 min, and then released hydrogen at 80 °C and a vacuum pressure not exceeding 10 Pa for 60 min, repeating the cycle 100 times. After cycling, the mass proportion of fine powder with a particle size less than 10 μm in the sample of Example 2 was 6.0%, lower than the 16.0% in the uncoated sample, indicating that the polydopamine-derived carbon layer can buffer the interfacial stress caused by the volume change of hydrogen absorption and desorption, and inhibit the breakage of TiMn particles and the formation of ultrafine powder.

[0059] Air stability was determined with the reversible hydrogen uptake capacity Q0 before exposure as 100%. After the sample was exposed to air at 25±2 ℃ and 50±10% relative humidity for 7 days, the reversible hydrogen uptake capacity Q was measured under the same hydrogen conditions of 25 ℃ and 3.0 MPa. 7d Example 2: Capacity retention rate Q of the sample 7d The / Q0 value was 94%, meaning that after 7 days of exposure, the reversible hydrogen absorption capacity remained at 94% of that before exposure. This indicates that the continuous PDA-derived nitrogen-doped carbon layer can reduce the direct contact between oxygen and water vapor and the TiMn surface.

[0060] The above results indicate that the polydopamine-derived nitrogen-doped carbon layer has good interfacial coverage and bonding ability, can stably fix expanded graphite and form interparticle thermal conduction pathways, and at the same time synergistically improve the bed thermal conductivity, hydrogen absorption kinetics, cycle anti-pulverization ability and air stability.

[0061] Example 3: Low-carbon content phenolic resin-derived carbon / expanded graphite composite coated TiMn-based hydrogen storage alloy particles This embodiment uses 50.0 g of commercial TiMn-based hydrogen storage alloy powder as a reference. The commercial TiMn-based hydrogen storage alloy was crushed and classified, and powder with a particle size of 30-80 μm was collected. The median particle size D of the obtained powder was... 50 The particle size is approximately 50 μm. Before use, the powder was vacuum dried at 100 °C and an absolute pressure not exceeding 100 Pa for 6 h, and then cooled to room temperature under argon protection. The median lateral dimension D of the expanded graphite microsheets used is... 50 The thickness is 10–20 μm (15 μm in this case), the apparent sheet thickness is 0.5–1.5 μm, and it is vacuum dried at 80 °C for 4 h before use.

[0062] 1) Preparation of the inner binder precursor: Weigh 0.50 g of methyl phenolic resin by solids and add it to 4.50 g of anhydrous ethanol. Stir mechanically at room temperature for 30 min to obtain a phenolic resin solution with a solids mass fraction of 10 wt%. The solids mass of the phenolic resin is 1.0 wt% of the mass of the TiMn-based hydrogen storage alloy powder.

[0063] 2) Phenolic resin pre-coating: 50.0 g of dried TiMn-based hydrogen storage alloy powder was placed in a SYH-1 type three-dimensional motion mixer or a mixing device with equivalent low-shear tumbling function, without adding grinding balls or other grinding media. Mixing was carried out at a speed of 40–60 r / min, 50 r / min in this example. The phenolic resin solution was sprayed onto the continuously tumbling TiMn powder surface using an atomizing nozzle over 8–12 min. After spraying, mixing continued for 15 min to allow partial evaporation of ethanol and adhesion of the phenolic resin precursor to the TiMn particle surface.

[0064] 3) Fixation of expanded graphite for external thermal bridges: While the phenolic resin precursor layer still has adhesive ability and the powder has no obvious free liquid, weigh 0.25 g of dried expanded graphite flakes and add them in 5 equal portions, 0.05 g each time. After each addition, continue mixing at 40–60 r / min (50 r / min in this case) for 3 min. After all the graphite has been added, continue mixing at 40–60 r / min (50 r / min in this case) for 20 min, so that the expanded graphite flakes adhere to the outside of the phenolic resin precursor layer and are partially exposed on the outer surface of the particles. The amount of expanded graphite added is 0.5 wt% of the mass of the TiMn-based hydrogen storage alloy powder.

[0065] 4) Drying, pre-curing, and carbonization: The obtained composite powder was spread evenly in a quartz boat, with a layer thickness not exceeding 8 mm (7 mm in this case), and vacuum dried at 80 ℃ for 4 h. Subsequently, under an Ar atmosphere, the temperature was increased to 120 ℃ at 1 ℃ / min and held for 1 h, then increased to 160 ℃ at 1 ℃ / min and held for 1 h to pre-cur the phenolic resin and fix the expanded graphite. Then, Ar with a volume purity of not less than 99.999% was introduced at a flow rate of 300 mL / min, and the temperature was increased to 200 ℃ at 2 ℃ / min and held for 1 h, then increased to 500 ℃ at 2 ℃ / min and held for 2 h to transform the phenolic resin into a non-graphitized internally bonded carbon layer. After the holding period, the powder was naturally cooled to room temperature under Ar protection to obtain low-carbon content PF-C / EG composite-coated TiMn-based hydrogen storage alloy powder.

[0066] In the samples obtained in this embodiment, the thickness of the inner bonding carbon layer is 50–200 nm, and the total carbon content is approximately 0.8–1.5 wt%. Tested using the same method as in Example 1, the effective thermal conductivity of the bed is higher than that of the uncoated TiMn sample and the sample coated only with phenolic resin-derived carbon, indicating that even with lower amounts of phenolic resin and expanded graphite, the external thermal bridge carbon material can still improve interparticle heat transfer after being fixed by the inner bonding layer.

[0067] Example 4: High-carbon-content phenolic resin-derived carbon / expanded graphite composite coated TiMn-based hydrogen storage alloy particles This embodiment uses 200.0 g of commercial TiMn-based hydrogen storage alloy powder as a basis. The commercial TiMn-based hydrogen storage alloy was crushed and graded, collecting powder with a particle size of 30–80 μm. The median particle size D50 of the obtained powder was approximately 50 μm. Before use, the powder was vacuum dried at 100 °C and an absolute pressure not exceeding 100 Pa for 6 h, and then cooled to room temperature under argon protection. The median lateral dimension D of the expanded graphite microsheets used is... 50 The thickness is 10–20 μm, the apparent thickness of the sheet is 0.5–1.5 μm, and it is vacuum dried at 80 °C for 4 h before use.

[0068] 1) Preparation of the inner binder precursor: Weigh 6.00 g of methyl phenolic resin by solids and add it to 24.00 g of anhydrous ethanol. Stir mechanically at room temperature for 30 min to obtain a phenolic resin solution with a solids mass fraction of 20 wt%. The solids mass of the phenolic resin is 3.0 wt% of the mass of the TiMn-based hydrogen storage alloy powder.

[0069] 2) Phenolic resin pre-coating: 200.0 g of dried TiMn-based hydrogen storage alloy powder was placed in a SYH-5 type three-dimensional motion mixer or a mixing device with equivalent low-shear tumbling function, without adding grinding balls or other grinding media. Mixing was carried out at a speed of 30–50 r / min; in this example, it was 40 r / min. A phenolic resin solution was sprayed onto the continuously tumbling TiMn powder surface using an atomizing nozzle over 20–30 min. After spraying, mixing continued for 20 min to allow partial evaporation of ethanol and uniform adhesion of the phenolic resin precursor to the TiMn particle surface.

[0070] 3) Fixation of expanded graphite with external thermal bridges: While the phenolic resin precursor layer still has adhesive ability and the powder remains dispersed, weigh 4.00 g of dried expanded graphite flakes and add them in 8 portions, 0.50 g each time, mixing for 3-5 min after each addition; after all the graphite has been added, continue mixing for 30 min to allow the expanded graphite flakes to adhere to the outside of the phenolic resin precursor layer, while retaining some flakes exposed on the outer surface of the particles. The amount of expanded graphite added is 2.0 wt% of the mass of the TiMn-based hydrogen storage alloy powder.

[0071] 4) Drying, pre-curing, and carbonization: The obtained composite powder was spread evenly in a quartz boat, with a layer thickness not exceeding 8 mm (6 mm in this case), and vacuum dried at 80 ℃ for 6 h. Subsequently, under an Ar atmosphere, the temperature was increased to 120 ℃ at 1 ℃ / min and held for 1 h, then increased to 160 ℃ at 1 ℃ / min and held for 2 h to allow the phenolic resin to fully cross-link and cure, fixing the expanded graphite to the particle surface. Then, Ar with a volume purity of not less than 99.999% was introduced at a flow rate of 300 mL / min, and the temperature was increased to 250 ℃ at 2 ℃ / min and held for 1 h, then increased to 600 ℃ at 2 ℃ / min and held for 2 h to transform the phenolic resin into a non-graphitized internally bonded carbon layer. After the holding period, the powder was naturally cooled to room temperature under Ar protection to obtain a high-carbon-content PF-C / EG composite-coated TiMn-based hydrogen storage alloy powder.

[0072] In the sample obtained in this embodiment, the thickness of the inner bonding carbon layer is 200–800 nm, and the total carbon content is approximately 3–5 wt%. Tested using the same method as in Example 1, the effective thermal conductivity of the bed in this sample is further improved or maintained at a high level compared to Example 1. However, due to the increased carbon content, its initial reversible hydrogen storage capacity may be lower than that of Example 1. This embodiment illustrates that the amount of phenolic resin and expanded graphite, as well as the carbonization temperature, can be adjusted within a certain range and can be balanced according to the requirements for enhanced thermal conductivity and capacity retention.

[0073] Example 5: Polydopamine-derived nitrogen-doped carbon / expanded graphite composite coated TiMn-based hydrogen storage alloy particles with low polydopamine dosage This embodiment uses 50.0 g of commercial TiMn-based hydrogen storage alloy powder as a reference. The commercial TiMn-based hydrogen storage alloy was crushed and classified, and powder with a particle size of 30-80 μm was collected. The median particle size D of the obtained powder was... 50 The particle size is approximately 50 μm. Before use, the powder was vacuum dried at 100 °C and an absolute pressure not exceeding 100 Pa for 6 h, and then cooled to room temperature under argon protection. The median lateral dimension D of the expanded graphite microsheets used is... 50 The thickness is 10–20 μm, the apparent thickness of the sheet is 0.5–1.5 μm, and it is vacuum dried at 80 °C for 4 h before use.

[0074] 1) Preparation of polydopamine deposition solution: Prepare 250 mL of Tris buffer with a concentration of 10 mmol / L, and adjust the pH to 8.0±0.1 with hydrochloric acid. Weigh 0.25 g of dopamine hydrochloride and add it to the above buffer to make the concentration of dopamine hydrochloride 1.0 mg / mL.

[0075] 2) Formation of the polydopamine thin binder layer: 50.0 g of dried TiMn-based hydrogen storage alloy powder was added to the above-mentioned dopamine solution. The mixture was then rolled at a low speed of 50–80 r / min or slowly mechanically stirred for 30 min at 20–25 °C to allow in-situ oxidative polymerization of dopamine on the surface of the TiMn particles. After the reaction, the mixture was immediately filtered, rinsed once with 50 mL of deionized water, and then twice with 50 mL of anhydrous ethanol to remove free polydopamine particles and replace surface moisture. After filtration, the particles were controlled to be in a semi-wet state, with a moist surface but no obvious free liquid.

[0076] 3) Fixation of the expanded graphite external thermal bridge layer: The obtained semi-wet TiMn@PDA particles are transferred to a low-shear three-dimensional motion mixer or roller coating equipment and rolled at 40–60 r / min (50 r / min in this case). 0.25 g of dried expanded graphite micro-flakes are weighed and added in 5 equal portions, 0.05 g each time, with rolling for 3 min after each addition; after all the addition is complete, rolling continues at 40–60 r / min (50 r / min in this case) for 20 min, so that the expanded graphite micro-flakes are fixed by the polydopamine wet layer and partially exposed on the outer surface of the particles. The amount of expanded graphite added is 0.5 wt% of the mass of the TiMn-based hydrogen storage alloy powder.

[0077] 4) Drying and carbonization: The obtained particles were spread evenly in a quartz boat, with a layer thickness not exceeding 8 mm (6 mm in this case), and vacuum dried at 60 ℃ for 6 h, followed by vacuum drying at 90 ℃ for another 1 h. The dried particles were placed in the constant temperature zone of a tube furnace, and Ar with a volume purity of not less than 99.999% was introduced at a flow rate of 300 mL / min for 30 min. The temperature was increased to 300 ℃ at 2 ℃ / min and held for 1 h, followed by increasing the temperature to 500 ℃ at 2 ℃ / min and holding for 2 h, so that polydopamine was converted into a nitrogen-doped carbon inner binder layer. After carbonization, the particles were naturally cooled to room temperature under Ar protection to obtain low PDA content PDA-C / EG composite coated TiMn-based hydrogen storage alloy powder.

[0078] In the sample obtained in this embodiment, the thickness of the nitrogen-doped carbon inner binder layer is 50–200 nm, and the total carbon content is approximately 0.8–1.5 wt%. Tested using the same method as in Example 1, the effective thermal conductivity of the sample bed is 0.72 W / (m·K), the maximum hydrogen absorption temperature rise is 14.2 °C, and the t90 After 460 s and 100 cycles, the proportion of fine powder with a particle size less than 10 μm was 9.5%, the capacity retention rate after 7 days of air exposure was 88%, and the initial reversible hydrogen storage capacity was 1.65 wt%. These results indicate that an effective carbon binder layer and external thermal bridge structure can still be formed under lower PDA concentration, shorter deposition time, and lower expanded graphite dosage, but the thermal conductivity enhancement and oxidation resistance are lower than in Example 2.

[0079] Example 6: Polydopamine-derived nitrogen-doped carbon / expanded graphite composite coated TiMn-based hydrogen storage alloy particles with higher polydopamine content This embodiment uses 200.0 g of commercial TiMn-based hydrogen storage alloy powder as a reference. The commercial TiMn-based hydrogen storage alloy was crushed and classified, and powder with a particle size of 30-80 μm was collected. The median particle size D of the obtained powder was... 50 The particle size is approximately 50 μm. Before use, the powder was vacuum dried at 100 °C and an absolute pressure not exceeding 100 Pa for 6 h, and then cooled to room temperature under argon protection. The median lateral dimension D of the expanded graphite microsheets used is... 50 The thickness is 10–20 μm, the apparent thickness of the sheet is 0.5–1.5 μm, and it is vacuum dried at 80 °C for 4 h before use.

[0080] 1) Preparation of polydopamine deposition solution: Prepare 1000 mL of Tris buffer with a concentration of 10 mmol / L, and adjust the pH to 9.0±0.1 with hydrochloric acid. Weigh 3.00 g of dopamine hydrochloride and add it to the above buffer to make the concentration of dopamine hydrochloride 3.0 mg / mL.

[0081] 2) Formation of the polydopamine binder layer: 200.0 g of dried TiMn-based hydrogen storage alloy powder was added to the above-mentioned dopamine solution. The mixture was then rolled at a low speed of 50–80 r / min (60 r / min in this case) or slowly stirred mechanically for 2 h at 20–25 °C to allow in-situ oxidative polymerization of dopamine on the surface of the TiMn particles, forming a relatively continuous polydopamine precursor layer. Immediately after the reaction, the mixture was filtered, rinsed once with 200 mL of deionized water, and then twice with 200 mL of anhydrous ethanol to remove free polydopamine particles and displace surface moisture. After filtration, the particles were controlled to be in a semi-wet state, with a moist surface but no obvious free liquid.

[0082] 3) Fixation of the expanded graphite external thermal bridge layer: The obtained semi-wet TiMn@PDA particles are transferred to a low-shear three-dimensional motion mixer or roller coating equipment and rolled at 30–50 r / min (40 r / min in this case). 4.00 g of dried expanded graphite flakes are weighed and added in 8 equal portions, 0.50 g each time. After each addition, the particles are rolled at 30–50 r / min (40 r / min in this case) for 3–5 min. After all the particles have been added, rolling continues for 30 min to stabilize the expanded graphite flakes under the wet polydopamine layer, while leaving some flakes exposed on the outer surface of the particles. The amount of expanded graphite added is 2.0 wt% of the mass of the TiMn-based hydrogen storage alloy powder.

[0083] 4) Drying and carbonization: The obtained particles were spread evenly in a quartz boat, with a layer thickness not exceeding 8 mm (6 mm in this case), and vacuum dried at 60 ℃ for 8 h, followed by vacuum drying at 90 ℃ for another 2 h. The dried particles were placed in the constant temperature zone of a tube furnace, and Ar with a volume purity of not less than 99.999% was introduced at a flow rate of 300 mL / min for 30 min. The temperature was increased to 300 ℃ at 2 ℃ / min and held for 1 h, followed by increasing the temperature to 600 ℃ at 2 ℃ / min and holding for 2 h, so that polydopamine was converted into a nitrogen-doped carbon inner binder layer. After carbonization, the particles were naturally cooled to room temperature under Ar protection to obtain a PDA-C / EG composite coated TiMn-based hydrogen storage alloy powder with a high PDA content.

[0084] In the sample obtained in this embodiment, the thickness of the nitrogen-doped carbon inner binder layer is 200–600 nm, and the total carbon content is approximately 3–5 wt%. Tested using the same method as in Example 1, the effective thermal conductivity of this sample bed is 0.84 W / (m·K), the maximum hydrogen absorption temperature rise is 12.4 °C, and the t 90 After 450 s and 100 cycles, the proportion of fine powder with a particle size less than 10 μm was 5.0%, the capacity retention rate after 7 days of air exposure was 96%, and the initial reversible hydrogen storage capacity was 1.57 wt%. These results indicate that appropriately increasing the PDA concentration, deposition time, and expanded graphite addition amount is beneficial for improving the fixation stability of expanded graphite, bed thermal conductivity, and air stability. However, increasing the total carbon content will have a certain dilutive effect on the initial reversible hydrogen storage capacity.

[0085] As shown in Table 1, the PF-C / EG composite coated sample of Example 1 has better overall hydrogen absorption kinetics. Example 4 has the highest effective thermal conductivity of the bed due to its higher carbon content and expanded graphite content. The PDA-C / EG samples of Examples 2 and 6 have better resistance to pulverization and air stability. Among them, Example 6 has the highest capacity retention rate, but the higher carbon content will lead to a decrease in the initial reversible hydrogen storage capacity.

[0086] Comparative Example The following comparative examples illustrate the advantages of the "inner bonding carbon layer + outer thermal bridge carbon layer" structure in this application compared to uncoated, simple mixing, and ordinary carbon coating methods.

[0087] Comparative Example 1: Uncoated TiMn-based hydrogen storage alloy particles Commercial TiMn-based hydrogen storage alloy particles were sieved to obtain particles with a diameter of 0.6–0.85 mm without any carbon coating treatment, which served as a blank control.

[0088] Compared to Examples 1 and 2, the uncoated TiMn-based hydrogen storage alloy particle bed mainly relies on point contact heat transfer between particles, resulting in a lower effective thermal conductivity. During hydrogen absorption, the local temperature rise within the bed is more significant, while during hydrogen release, external heat transfer to the bed interior is slower. Furthermore, after cyclic hydrogen absorption and release, the particles are more prone to cracking and fine powder formation, leading to further attenuation of the bed's thermal conductivity.

[0089] Comparative Example 2: Simple physical mixing of TiMn-based hydrogen storage alloy particles with expanded graphite TiMn-based hydrogen storage alloy particles with a particle size of 30-80 μm were mechanically mixed at a low speed of 50-80 r / min (60 r / min in this case) for 15 min with expanded graphite at 1 wt% relative to the mass of the TiMn-based hydrogen storage alloy particles. No phenolic resin, polydopamine or other internal binder precursors were added, and no carbonization fixation treatment was performed.

[0090] Compared to Example 1, the expanded graphite in the simple physical mixture sample cannot be stably fixed on the surface of TiMn-based hydrogen storage alloy particles, and tends to be distributed in bed pores or local agglomeration areas, not necessarily preferentially located at the particle contact interface. After loading vibration or hydrogen absorption / desorption cycling, the expanded graphite is prone to migration, resulting in insufficient thermal conductivity network stability. Therefore, with the same amount of expanded graphite added, the effective thermal conductivity of the bed and the retention of thermal conductivity after cycling in this comparative example are lower than those in Example 1.

[0091] Comparative Example 3: Phenolic resin-derived carbon-coated TiMn-based hydrogen storage alloy particles only Samples were prepared according to the method of Example 1, with the same process and conditions as Example 1, except that expanded graphite was not added, and only phenolic resin was used as the carbon precursor (i.e., step 3 was omitted). Steps 4) and 5) were performed directly after steps 1) and 2). After drying, pre-curing and carbonization at 550 °C in an Ar atmosphere, TiMn-based hydrogen storage alloy particles coated with only phenolic resin-derived carbon were obtained.

[0092] The phenolic resin-derived carbon layer formed on the sample surface can improve the surface stability of particles to a certain extent and has a certain antioxidant effect. However, this carbon layer is mainly a non-graphitized carbon layer with limited thermal conductivity and is difficult to form a long-range thermal bridge network between particles. Compared with Example 1, the effective thermal conductivity of the bed in this comparative example is only slightly improved, indicating that the external thermal bridge expanded graphite plays a key role in reducing the contact thermal resistance between particles.

[0093] Comparative Example 4: PF-C / EG composite coated TiMn-based hydrogen storage alloy particles with low phenolic resin content The sample was prepared according to the method of Example 1, with the same process and conditions as Example 1, except that the amount of solid phenolic resin added was reduced from 2.00 g to 0.20 g, i.e., the solid mass of phenolic resin was 0.2 wt% of the mass of TiMn-based hydrogen storage alloy powder; the amount of expanded graphite microsheets added remained at 1.00 g, reducing the mass ratio of the inner binder precursor to the outer thermal bridge carbon material from 2:1 in Example 1 to 0.2:1. The remaining conditions for spraying, batch addition of expanded graphite, drying, pre-curing, and carbonization at 550℃ were the same as in Example 1. The effective thermal conductivity of the sample bed was 0.70 W / (m·K), the maximum hydrogen absorption temperature was 14.6℃, and the t 90 After 480 s and 100 cycles, the proportion of fine powder with a particle size less than 10 μm was 13.0%, and the capacity retention rate was 84% ​​after 7 days of air exposure.

[0094] Because the amount of phenolic resin is too low, it is difficult to form a continuous inner carbon layer with sufficient bonding strength on the surface of TiMn particles. Expanded graphite is prone to detachment or migration during loading and circulation, resulting in lower integrity and stability of the interparticle thermal bridge network compared to Example 1. This comparative example illustrates the importance of the amount of inner binder and the mass ratio of inner to outer layers in fixing the external thermal bridge carbon material and the thermal conductivity of the bed.

[0095] Comparative Example 5: PDA-C / EG Composite Coated TiMn-based Hydrogen Storage Alloy Particles with Excessive Polydopamine Deposition The sample was prepared according to the method of Example 2, with the same process and conditions as Example 2, except that the dopamine hydrochloride concentration was increased from 2.0 mg / mL to 5.0 mg / mL, and the polymerization deposition time was extended from 60 min to 6 h; the amount of expanded graphite microsheets added remained 1.00 g, and the remaining washing, semi-drying, batch fixation of expanded graphite, drying, and carbonization conditions at 550 °C were the same as in Example 2. The effective thermal conductivity of the sample bed was 0.78 W / (m·K), the maximum hydrogen absorption temperature was 13.0 °C, and the t 90After 520 s and 100 cycles, the proportion of fine powder with a particle size of less than 10 μm was 5.5%, the capacity retention rate after 7 days of air exposure was 95%, and the initial reversible hydrogen storage capacity was 1.55 wt%.

[0096] Higher dopamine concentrations and longer deposition times result in a thicker polydopamine precursor layer on the surface of TiMn particles, leading to a corresponding increase in the thickness of the inner binder carbon layer and the total carbon content after carbonization. While this structure improves the adhesion stability of expanded graphite, the excessively thick inner carbon layer increases the mass transfer resistance of hydrogen to the TiMn alloy surface and exacerbates the dilution of reversible hydrogen storage capacity by non-hydrogen storage components, resulting in lower hydrogen absorption kinetics and initial reversible hydrogen storage capacity compared to Example 2. This comparative example illustrates the need to control the polydopamine concentration and deposition time within reasonable ranges.

[0097] From the above comparative examples and embodiments, it can be concluded that the uncoated TiMn sample bed has the lowest effective thermal conductivity, at 0.55 W / (m·K). 90 The thermal conductivity was 600 s, indicating poor bed heat transfer. Simply adding expanded graphite increased the thermal conductivity to 0.68 W / (m·K), but the fine powder proportion remained at 14.0% after cycling, indicating insufficient stability of the unfixed expanded graphite thermal network. Only the phenolic resin-derived carbon-coated sample showed a reduction in fine powder proportion to 10.0% and an increase in capacity retention to 89% after air exposure, but its thermal conductivity was only 0.61 W / (m·K), indicating that the inner carbon layer alone mainly improves anti-pulverization and anti-oxidation, with limited thermal conductivity enhancement. The PF-C / EG sample in Example 1 had the highest thermal conductivity, reaching 0.82 W / (m·K), and its highest temperature fluctuated to 12.6 °C. 90 The shortening of the time to 410 s indicates the best thermal conductivity enhancement effect. The PDA-C / EG sample in Example 2 has a thermal conductivity of 0.76 W / (m·K), but the lowest fine powder ratio is 6.0%, while the highest air exposure capacity retention rate is 94%, indicating superior resistance to powdering and air stability. In Examples 1 and 2, the thickness of the inner binder carbon layer is controlled at approximately 100–300 nm, which balances expanded graphite fixation, hydrogen mass transfer, and hydrogen storage capacity. Comparative Examples 4 and 5 further illustrate that too little inner binder layer leads to weak expanded graphite fixation, while a thickness greater than approximately 500 nm reduces hydrogen absorption kinetics and hydrogen storage capacity. Therefore, the synergistic construction of an appropriate amount of inner binder carbon layer and exposed expanded graphite thermal bridge layer is key to simultaneously improving bed thermal conductivity, hydrogen absorption kinetics, cycle stability, and air stability.

Claims

1. A carbon-coated TiMn-based hydrogen storage alloy particle, characterized in that: The carbon-coated TiMn-based hydrogen storage alloy particles include a TiMn-based hydrogen storage alloy core, an inner bonding carbon layer disposed on the surface of the TiMn-based hydrogen storage alloy core, and an outer thermal bridge carbon layer disposed on the outer surface of the inner bonding carbon layer away from the core.

2. The carbon-coated TiMn-based hydrogen storage alloy particles according to claim 1, characterized in that: The TiMn-based hydrogen storage alloy is TiMn, TiMn2, or TiMn. 1.5 TiMn-based alloys containing one or more active phases selected from TiMnCr, TiMnV, and TiMnCrV, or the aforementioned active phases further containing one or more elements selected from Cr, V, Fe, Zr, Ni, Co, Mo, Al, La, and Ce. The particle size of the TiMn-based hydrogen storage alloy particles is 10–300 μm, preferably 20–100 μm, and more preferably 30–80 μm; preferably, the median particle size D50 of the TiMn-based hydrogen storage alloy particles is 40–65 μm.

3. The carbon-coated TiMn-based hydrogen storage alloy particles according to claim 1, characterized in that: The inner bonding carbon layer is formed by pyrolysis of one or more of phenolic resin (preferably methyl phenolic resin) or polydopamine; Different precursors are coated using separate, defined processes: phenolic resin is coated in the form of a solution or dispersion of an organic solvent; polydopamine is formed by in-situ oxidative polymerization of dopamine on the surface of TiMn particles in a weakly alkaline aqueous solution with a pH of 8.0–9.0 (preferably 8.5 ± 0.1); the inner bonding carbon layer is used to fix the external thermal bridge carbon material and buffer the interfacial stress of the TiMn-based hydrogen storage alloy during hydrogen absorption and desorption cycles. The thickness of the inner bonding carbon layer is 5–1000 nm, preferably 50–500 nm, and more preferably 100–300 nm; the inner bonding carbon layer may be a non-graphitized carbon layer derived from phenolic resin, or one or more of a nitrogen-containing carbon layer derived from polydopamine.

4. The carbon-coated TiMn-based hydrogen storage alloy particles according to claim 1, characterized in that: The external thermal bridge carbon layer includes one or both of expanded graphite and graphene; the lateral dimension of the expanded graphite sheet in the unloaded state is 5 to 30 μm, preferably 10 to 20 μm; The apparent sheet thickness is 0.2–3 μm, preferably 0.5–1.5 μm; the lateral dimension of the graphene sheet in the unloaded state is 0.5–15 μm, preferably 2–8 μm, the sheet thickness is 1–30 nm, preferably 2–15 nm, and the number of layers is preferably 2–50, preferably 3–20. The median lateral dimension of the expanded graphite sheet is 5–30 μm, preferably 10–20 μm.

5. The carbon-coated TiMn-based hydrogen storage alloy particles according to claim 1 or 4, characterized in that: The external thermal bridge carbon layer is at least partially exposed on the outer surface of the particles, so that when multiple carbon-coated TiMn-based hydrogen storage alloy particles are stacked to form a hydrogen storage bed, the external thermal bridge carbon layers on the surfaces of adjacent particles can contact each other, overlap, entangle or form surface contact, thereby forming a continuous or semi-continuous inter-particle thermal bridge network. Preferably, the ratio of the median lateral dimension of the expanded graphite sheet to the median particle size of the TiMn-based hydrogen storage alloy particle is 0.10 to 0.60, more preferably 0.20 to 0.40, so that the expanded graphite can adhere to the surface of a single TiMn particle and continuously overlap between adjacent particles through multiple sheets, rather than occupying the bed pores with excessively large independent agglomerates.

6. The carbon-coated TiMn-based hydrogen storage alloy particles according to claim 1, characterized in that: The total carbon content of the carbon-coated TiMn-based hydrogen storage alloy particles is 0.2–10 wt%, preferably 0.5–5 wt%, and more preferably 0.8–3 wt%; the mass of expanded graphite and / or graphene in the external thermal bridge carbon layer is 0.1–5 wt% of the mass of the TiMn-based hydrogen storage alloy particles, preferably 0.3–3 wt%, and more preferably 0.5–2 wt%.

7. The carbon-coated TiMn-based hydrogen storage alloy particles according to claim 1, characterized in that: The inner bonding carbon layer is not the main thermally conductive phase, but a non-graphitized carbon layer and / or nitrogen-doped carbon layer formed by the pyrolysis of phenolic resin and / or polydopamine. It is used to fix the external thermal bridge carbon material and provide a certain degree of anti-oxidation and anti-pulverization buffer. The external thermal bridge carbon layer is the main thermally conductive phase, which forms a thermally conductive network between particles through lamellar overlap, tubular entanglement or surface contact.

8. A method for preparing carbon-coated TiMn-based hydrogen storage alloy particles as described in claim 1, characterized in that: Includes the following steps: (1) The TiMn-based hydrogen storage alloy is crushed and the particle size is controlled by standard sieving or air classification to obtain TiMn-based hydrogen storage alloy particles. The obtained TiMn-based hydrogen storage alloy particles were dried; after processing, they were cooled to room temperature under an inert atmosphere and stored in a sealed container. (2) An adhesive inner bonding layer is formed on the surface of TiMn-based hydrogen storage alloy particles: the precursor carbon source of the inner bonding layer is dopamine or phenolic resin. When the carbon source is phenolic resin, the phenolic resin is in the form of a solution, dispersion or flowable slurry of phenolic resin and is brought into contact with TiMn-based hydrogen storage alloy particles in a rolling state by spraying, dripping, impregnation or atomizing spraying, and then rolled coating is performed. 60% to 95% of the solvent is removed so that there is no free-flowing liquid on the particle surface and the particles remain dispersed and the inner bonding layer precursor layer has adhesiveness. When the carbon source is dopamine, TiMn-based hydrogen storage alloy particles are placed in an alkaline dopamine solution for in-situ oxidative polymerization. After filtration and rinsing, free polydopamine particles are removed and surface moisture is replaced, so that the particles are in a semi-wet state with a wet surface but no obvious free liquid. (3) Add the external thermal bridge carbon material to the particles obtained in step (2) while they are rolling, so that the external thermal bridge carbon material is attached to the outside of the inner adhesive layer. (4) After drying and pre-curing, carbonization is carried out to transform the inner bonding layer into a carbon-based inner bonding layer. At the same time, the external thermal bridge carbon material is fixed on the outer surface of the particles to obtain carbon-coated TiMn-based hydrogen storage alloy particles with the ability to construct inter-particle thermal bridge networks.

9. The preparation method according to claim 8, characterized in that: In step (1): TiMn-based hydrogen storage alloy particles with a particle size of 10–300 μm, preferably 20–100 μm, and more preferably 30–80 μm, are obtained by standard sieving or air classification. Preferably, the median particle size D of the particles is... 50 The thickness is 40–65 μm. The drying conditions are: vacuum drying at 80–120 °C and absolute pressure not higher than (less than or equal to) 100 Pa for 4–8 h, or treatment in an inert atmosphere at 80–200 °C for 1–4 h, or treatment in an H2 / Ar mixed atmosphere containing 1–10 vol.% H2 at 100–250 °C for 0.5–2 h, to remove adsorbed water, weakly adsorbed gases and loose surface impurities; The inert atmosphere is one or more of nitrogen and argon. In step (2): The phenolic resin solution is a phenolic resin solution with a solid mass fraction of 5-20 wt% obtained by mixing solid phenolic resin with anhydrous ethanol; if it is a commercial phenolic resin solution, the amount added is calculated according to its actual solid content, so that the amount of solid phenolic resin added is 0.2% to 8% of the mass of TiMn-based hydrogen storage alloy particles, preferably 0.5% to 5%, more preferably 1% to 3%; The alkaline dopamine solution is prepared by adding dopamine hydrochloride to a buffer solution to achieve a dopamine concentration of 1.0-3.0 mg / mL. The buffer solution is Tris buffer, and the pH is adjusted to 8.0-9.0, preferably 8.5±0.

1. When the carbon source is phenolic resin, the rolling state is as follows: the TiMn-based hydrogen storage alloy particles are placed in the mixing device at a rotation speed of 10-80 rpm, preferably 20-50 rpm; the temperature of the TiMn-based hydrogen storage alloy particles is 15-60 ℃; and the rolling coating time is 10-120 min, preferably 30-60 min. When the carbon source is dopamine, the conditions for in-situ oxidative polymerization are 20-25 °C, low-speed rolling or slow mechanical stirring at 50-80 r / min for 30-120 min. In step (3): The rolling process is carried out in a mixing device at 15–60 °C and 10–80 rpm; the external heat bridge carbon material is added in stages, with rolling continuing for 3–10 minutes after each addition, and rolling continuing for 5–60 minutes after all the external heat bridge carbon material has been added; the amount of external heat bridge carbon material added is 0.1%–5% of the mass of the TiMn-based hydrogen storage alloy particles; Step (4) specifically includes: A. Drying and pre-curing: Vacuum drying at 60-90 ℃ for 2-12 h; followed by heat treatment from room temperature to the heat treatment temperature; The heat treatment atmosphere is preferably one or more of Ar, He, H2 volume concentration of 1-10% H2 / Ar or H2 volume concentration of 1-10% H2 / He; The heat treatment temperature is 110–180 ℃, preferably 120–180 ℃; the heat treatment time is 0.5–5 h, preferably 1–3 h; the heating rate is preferably 1–3 ℃ / min. B. Carbonization treatment: The pre-cured particles are heated to 200-300℃ and held at that temperature for 0.5-2 h, and then heated to the carbonization temperature for carbonization. The carbonization atmosphere is preferably one or more of Ar and He. The carbonization temperature is 400-700℃, preferably 500-600℃. The carbonization time is 0.5-5 h, preferably 1-3 h. The mixing equipment is a drum coating equipment, disc coating equipment, V-shaped mixing equipment, or fluidized bed coating equipment that does not contain grinding media.

10. An application of the carbon-coated TiMn-based hydrogen storage alloy particles according to claim 1, characterized in that: Applications of carbon-coated TiMn-based hydrogen storage alloy particles in solid-state hydrogen storage devices, hydrogen compression devices, fuel cell hydrogen supply systems, mobile hydrogen source systems, stationary energy storage systems, or metal hydride hydrogen storage beds.